Korelasi Antara Gaya Hidup Hedonis dan Perilaku Konsumtif di Kalangan Mahasiswa dalam Perspektif Ekonomi Syariah - Hadi, Kartika Candra Kirana; Setiawan, Romi Adetio; Yustati, Herlina (Universitas Batanghari Jambi, 2024)
The aim of this study is to evaluate the influence of hedonistic lifestyles on consumer behavior among university students while analyzing the Islamic perspective regarding this behavior. Hedonism, as a lifestyle choice, captivates the interest of young individuals by offering a luxurious, comfortable, and abundant way of life without requiring substantial effort. Employing a quantitative method and applying Probability Sampling among 200 students, the research extracted a sample size of 115 individuals. The research findings illustrate a positive correlation between hedonistic lifestyles and consumer behavior, evidenced by the positive coefficients within the analysis. The more prevalent the hedonistic lifestyle, the more pronounced the consumer behavior becomes. A significant portion of the student community tends to be influenced by hedonistic tendencies, emphasizing pleasure over essential needs, consequently leading to consumer behavior. The activities, interests, and perspectives of the majority of students do not entirely align with the principles of Islamic economics, which emphasize the necessity for rational needs aligned with the Islamic sharia, as stated in the Quran (Al-A'raf verse 31). This signifies that the orientation of needs driven by hedonistic lifestyles contradicts the principles of Islamic economics that emphasize needs in line with positive values within Islamic teachings.